Mandating the use of the electric taxis: The case of Florence. (February 2020) - Scorrano, Mariangela; Danielis, Romeo; Giansoldati, Marco
Highlights: The city of Florence mandated the use of electric vehicles for the taxi service. We evaluate the cost-competitiveness of e-taxis using field data. The Florence e-taxi fleet has an average TCO/km lower than hybrid and diesel taxis. With MSRP, e-taxis need financial incentives or high annual distance travelled. Abstract: This paper discusses a policy enacted in 2016 by the city of Florence mandating the use of electric vehicles for the taxi service. We interviewed the taxi license owners (carriers), their co-operatives and the city administrators to evaluate the policy implementation, its acceptability and the cost-competitiveness of electric taxis (e-taxis) with respect to their hybrid and diesel alternatives. Using the data collected during the interviews, we estimated the total cost of ownership (TCO) of e-taxis and their conventional counterparts for the models comprising the Florence taxi fleet. We find that e-taxis already represent a valid alternative to the conventional ones not only from an environmental point of view but also from a private economic one. In particular, when the Florence-specific discounted purchase prices are considered and the base case scenario applies, e-taxis are the cheapest choice in terms of TCO and no financial incentives are needed. When the manufacturer suggested retail prices are considered, e-taxis are slightly less cost-competitive than hybrid taxis but more cost-competitive than the diesel ones. Sensitivity analyses are performed to evaluate the impact of the annual distance travelled, Ecobonus purchase subsidy, net revenue loss, annual percentage rate charged to finance the taxi acquisition and insurance premium.